Adjustment disorder and type-specific cancer incidence: a Danish cohort study. (3rd October 2018) - Ahern, Thomas P.; Veres, Katalin; Jiang, Tammy; Farkas, Dóra Körmendiné; Lash, Timothy L.; Sørensen, Henrik Toft; Gradus, Jaimie L.
Abstract: Background: Although adjustment disorder is common, there is a dearth of research on its physical health consequences. Earlier studies, biological mechanisms and stress-related behaviors suggest that cancer may be a potential sequelae of adjustment disorder. This study examined the association between adjustment disorder and type-specific cancer incidence in a nationwide cohort. Methods: Data were obtained from the comprehensive nationwide medical and administrative registries of Denmark. We calculated the incidence of type-specific cancers from 1995 to 2013 in patients with a prior adjustment disorder diagnosis ( n  = 58, 712), and compared it with the incidence in the general population by calculating standardized incidence ratios (SIRs) with accompanying 95% confidence intervals (CIs). SIRs were adjusted using semi-Bayes shrinkage. Results: The SIR for any type of cancer was 1.0 (95% CI: 0.99, 1.1). Adjustment disorder was associated with a 10% lower rate of immune-related cancers (SIR = 0.9, 95% CI: 0.84, 0.97) and with a 20% higher rate of smoking- and alcohol-related cancers (SIR = 1.2, 95% CI: 1.1, 1.3). We found null associations for hematological (SIR = 1.1, 95% CI: 0.89, 1.3) and hormone-related (SIR = 0.98, 95% CI: 0.91, 1.1) malignancies. After semi-Bayes adjustment, type-specific cancer SIRs indicated no association between adjustment disorder and cancer incidence. Conclusions: This study provides persuasive evidence for a null association between adjustment disorder and type-specific cancer incidence in a nationwide study cohort.